(untitled) (Fiep Bulletin - online, 2015)
Gyms are extremely visible places in the field of Physical Education. They not only concentrate many professionals and offer great diversity of physical activities, but also represent a well-recognized space associated with the cult to the body from multiple perspectives. The objectives of this research are: a) to identify and analyze which aspects have been privileged in the work developed by the Physical Education teachers in fitness centers; b) verify and discuss whether the teachers interfere in their students’ body vision. This qualitatively oriented research was carried out in Rio de Janeiro, in the four main fitness centers in the city’s west zone. Seventeen (17) teachers were selected through pre-established criteria, and semi-structures interviews were applied to them. The results have demonstrated that: a) the gym teachers who work in the field of fitness prioritize the technical and health aspects in their professional intervention: b) the aesthetical objectives seem to be the students’ but not the teachers’ main concern; c) most teachers believe they interfere in their students’ body vision, changing or influencing the way their students deal with their bodies. It was concluded that the nature of the teachers’ intervention is closer to the technical-biological paradigm prevalent in the Physical Education field since the pedagogical aspects did not emerge in their speeches. Besides, the relationship between teacher and student has a commercial aspect that may influence the Physical Education teachers’ action.